Analisis Model Kesuksesan Sistem Informasi Studi Kasus : Penggunaan SAP Pada PT Multimas Nabati Asahan - Erwin Setiawan Panjaitan; Dwi Tio Riky Julprianto Hutabarat; Lidya Veronica Hutabarat; Desi Arisandy (Jurnal SIFO Mikroskil, 2017)
This research was conducted by adopting Update IS Success Model that has been designed by DeLone and McLean (2003) by taking some necessary variables. The purpose of this research is to test the influence of system quality, information quality, and service quality toward users satisfaction of information system SAP. A sample which was used in this research was staff employee who using SAP. A sample of engineering which non probability sampling and used saturated method where all of the respondent being a sample in this research as big as so respondent. This research was using quantitative method research and analysing data which used i.e multiple regression linear. Testing hypotheses in this research was conducted by testing the effect of system quality, information quality, service quality toward user satisfaction and satisfaction effect of toward individual performance through partial test (t test) the research result was proving that partially. System quality wasn?¢â?¬â?¢t influenced and not significant toward user satisfaction, information quality wasn?¢â?¬â?¢t influenced and not significant toward user satisfaction, service quality was positive influential and significant toward user satisfaction, user satisfaction was positive influential and significant toward individual performance. ???  ???